PERAN GADGET DALAM MENINGKATKAN KUALITAS PEMBELAJARAN ONLINE DI ERA REVOLUSI INDUSTRI 4.0 - Neneng Nurmalasari (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2020)
This paper explains the importance of education in the world today. And education is designed for students so that they can meet their future well. A good future cannot be achieved if the quality of learning is not good either. In the current 4.0 revolution era, education is demanded to be more innovative and creative in utilizing technology as a medium of learning. Because technology is no longer a 'tool' but is embedded in people's lives this must be emphasized in students. In relation to improving the quality of online learning, gadgets are used as additional, supporting, and alternative support in improving the quality of learning.